Physics of energy conversion - Krischer, K.; Schönleber, Konrad (De Gruyter textbook., 2015)
Covers the physical basis of the most important energy conversion processes used for energy supply. Provides the fundamentals and a scientific understanding of the physics behind thermal power plants, solar cells and power plants, batteries and fuels cells as well as energy storage devices.